AN ANALYSIS ON THE COMPATIBILITY OF THE TEXTBOOK, DEVELOPING ENGLISH COMPETENCIES, WITH THE SCHOOL LEVEL-BASED CURRICULUM - Adhasih, Lulu Nur (2011)
This research paper is mainly intended to find out whether the English textbook used for the first year student of senior high school Developing English Competencies, SMA Book X develops the skills suggested by the school level-based curriculum. In line with the objectives of the research, the writer used a comparative method qualitatively. In collecting the data, she used document as data source. The data were analyzed by these steps: (1) finding out the kinds of skill available on the textbook, (2) classifying them, (3) analyzing them, (4) giving percentage from the total number, (5) judging whether the data are appropriate with indicators in School Level-based Curriculum or not, and (6) drawing conclusion and proposing suggestions. The result of the analysis shows that the percentage of the appropriateness of the skills developed in the textbook is 61%. It means that the textbook is good in developing skill demanded by the School Level-based Curriculum or compatible with the School Level-based Curriculum in developing skills. However the teacher should supply the textbook with other books which are much better in order to achieve the goal of teaching English. The writer of the textbook should revise the textbook and add more texts and activities to increase the quality of the textbook.